Hospital costs in the US for pulmonary mycobacterial diseases - Mirsaeidi, Mehdi (Int J Mycobacteriol, 2015)
BACKGROUND: Pulmonary mycobacterial diseases describe both tuberculosis (TB) and nontuberculous mycobacteria (NTM). Few data are available measuring the cost burden of mycobacterial diseases at the national level. The purpose of this study is to evaluate the cost burden and measure emerging trends in hospitalization of pulmonary TB and NTM cases in the United States from 2001 through 2012. METHODS: This study is a retrospective, community-based cost analysis of hospitalized patients with a principal diagnosis of pulmonary mycobacterial diseases from 2001 through 2012. Data for pulmonary TB and NTM were retrieved from the Healthcare Cost and Utilization Project (HCUP), US Department of Health and Human Services. The statistical significance of observed trends of NTM and TB national hospital costs was calculated using Poisson log-linear regression. RESULTS: 20,049 hospital discharges were reported for pulmonary NTM and 69,257 for pulmonary TB in the US from 2001 through 2012. The total associated cost of these discharges was $903,767,292 for pulmonary NTM and $2,078,113,317 for pulmonary TB. During the study period, the national hospital costs of pulmonary NTM increased at a statistically significant rate in the US over each year (P = 0.001). However, no such increase was found for national hospital costs of pulmonary TB. CONCLUSIONS: The national hospital cost of NTM management is increasing. These results emphasize the importance of continued research in pulmonary NTM in order to improve current guidelines in prevention and treatment strategies.